Paradigm of Multicultural Islamic Education Sociological Perspective - Nur Syam; Muh. Yusrol Fahmi (Jurnal Ijtihad, 2023)
The current era is multicultural education, and more specifically Islamic multicultural education. Complexity, rapid social change, the era of information technology in the midst of plurality and multiculturality of Indonesian society, so multicultural education becomes very important and relevant. Therefore, prioritizing education in this style becomes an obligation for the Ministry of Education and the Ministry of Religion and higher education institutions in Indonesia. In the framework of enriching studies and also implementing multicultural education, paradigmatic thinking is needed. From a sociological perspective, there are several paradigms, such as the social fact paradigm of multicultural education, the social definition paradigm of multicultural education and the social behavior paradigm of multicultural education. From this paradigm, research and studies can certainly be carried out to develop theories and praxis of multicultural Islamic education.